2021
DOI: 10.1155/2021/6622028
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Movement Restrictions on the Road Traffic in the Czech Republic during the State of Emergency

Abstract: The COVID-19 pandemic crisis has impacted numerous areas of people’s work and free-time activities. This article aims to present the main impacts of the COVID-19 movement restrictions on the road traffic in the Czech Republic, measured during the first epidemic wave, i.e., from 12 March to 17 May 2020. The state of emergency was imposed by the Czech government as a de jure measure for coping with the perceived crisis, although the measure eventually resulted only in a quite liberal de facto form of stay-at-hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…Travel protocols and other government provisions such as social distancing made it difficult for fishers to operate, resulting in limited operation time. With these limitations, the volume of fish caught started to decrease ( Jomitol, 2020 ; Simunek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Travel protocols and other government provisions such as social distancing made it difficult for fishers to operate, resulting in limited operation time. With these limitations, the volume of fish caught started to decrease ( Jomitol, 2020 ; Simunek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ECQ meant "stay at home" as mobility and transportation (air, water, and land) were restricted (Ferrer et al, 2021). It affected people's daily activity patterns or regular movements and habits from jogging, walking to dining in restaurants, which were previously thought normal or usual (Simunek et al, 2021). In the fisheries, movement restrictions significantly affected the fishers and also affected fish supply and demand, including fish distribution, labor and production of fish (Love et al, 2020;Belton et al, 2021).…”
Section: Covid-19 and Movement Restrictionsmentioning
confidence: 99%
“…Smallscale fisheries contribute to coastal communities' social and economic development as they provide food, livelihood, and income to the poor, vulnerable and marginal sectors (FAO, 2020a;Ferrer et al, 2021). However, severe implications of COVID-19 for the SSF have become more obvious (Simunek et al, 2021). Fishing area restrictions due to the implementation of border lockdowns was a major problem experienced by the fishers in Davao Gulf (Jomitol et al, 2020), complete shutdowns of fisheries were also experienced, stay-at-home orders preventing travel to and within fishing areas during imposition of draconian measures of lockdown (Okyere et al, 2020).…”
Section: Impacts Of Covid-19 Restrictions On the Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation
“…During an outbreak of the disease, government-imposed movement restrictions or self-imposed travel willingness would reduce human activity intensity. This indicated that the outbreak would be followed by a reduction in human activity intensity as well [ 30 , 31 ]. Therefore, we would explore the patterns of the disease cases and the check-ins to uncover the relationship between the two sets of time series.…”
Section: Introductionmentioning
confidence: 99%